2001
DOI: 10.1037/0097-7403.27.2.137
|View full text |Cite
|
Sign up to set email alerts
|

Relative validity of contextual and discrete cues.

Abstract: Contextual conditioning during relative validity training was explored in 3 experiments that used an appetitive Pavlovian conditioning preparation with rats. Magazine entries were the conditioned response. In Experiment 1, true-discrimination (TD: AX+, BX-) training generated weaker conditioning of X than did pseudodiscrimination (PD: AX+/-, BX+/-) training. The context showed a similar relative validity effect. Also, both PD training and simple partial reinforcement (X+/-) reduced contextual conditioning more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 41 publications
2
19
0
1
Order By: Relevance
“…Therefore, it is not clear what the cause of increased pre-CS responding might be. Indeed, a study examining another cue competition effect, relative validity, found a result that is the opposite of this effect ( Murphy et al, 2001 ). Thus, rats that received a discrimination between compounds AX+ and BX− (in which A, B and X were discrete cues) showed weaker responding to X and during the pre-CS interval compared to a group that received partial reinforcement of the compounds, AX+/− and BX+/−, suggesting that A and B had reduced learning of X and the contextual cues.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is not clear what the cause of increased pre-CS responding might be. Indeed, a study examining another cue competition effect, relative validity, found a result that is the opposite of this effect ( Murphy et al, 2001 ). Thus, rats that received a discrimination between compounds AX+ and BX− (in which A, B and X were discrete cues) showed weaker responding to X and during the pre-CS interval compared to a group that received partial reinforcement of the compounds, AX+/− and BX+/−, suggesting that A and B had reduced learning of X and the contextual cues.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, because the target stimu-lus X is always present, it provides an analogue to the context and provides a number of advantages in terms of assessing behavior controlled by it. Elsewhere we have taken advantage of this analogy (Murphy, Baker, & Fouquet, 2001b; see also Murphy & Baker, 2004).…”
mentioning
confidence: 98%
“…From this perspective, switching the context leads to a decrease in the associative strength accrued by the new stimulus compound (CS+New Context) presented at testing, and explains the decrease in conditioned responding related to the context switch (e.g., León et al, 2011;León, Callejas-Aguilera, & Rosas, 2012;Moreno-Fernández, Abad, Ramos-Álvarez, & Rosas, 2011;Murphy, Baker, & Fouquet, 2001). For instance, León et al (2011) explored the role of the length of training on the context-switch effect within a human predictive learning task.…”
mentioning
confidence: 99%